Brazilian Photographic Figure Rating Scale for Men: Psychometric Investigation - Castro, Marcela R. de; Morgado, Fabiane F. R.; Freitas Jr, Ismael F. [UNESP] (Sage Publications Inc, 2018)
As a follow-up to an earlier study from this research group involving women, this study examined the reliability and validity of the Brazilian Photographic Figure Rating Scale for Men (BPFRS-M) for evaluating men's body perception and dissatisfaction. In both versions of the Brazilian Photographic Figure Rating Scale (BPFRS), respondents viewed eight photographic images (seven distorted and one accurate) of themselves in standard poses and then offered self-ratings. In both versions, 10 experts assessed content validity and demonstrated high agreement (defined by ratings of 4-5 on a 5-point scale) that BPFRS items measured underlying constructs: and experts showed high (>70%) interrater agreement. For this version, participants were 149 Brazilian men (Mean=22.4; SD=2.7 years). Pearson correlations demonstrated convergence between the BPFRS-M and two related scales of men's body image. Positive correlations (p=.0001) were found between actual and respondent-perceived body mass index (BMI). Test-retest and Kappa Index confirmed temporal stability. The BPFRS-M can accurately and reliably assess body perception and dissatisfaction in young men.
Keywords: body image; body dissatisfaction; perception